Adult Brainstem Gliomas With H3K27M Mutation: Radiology, Pathology, and Prognosis - Daoud, Elena V; Rajaram, Veena; Cai, Chunyu; Oberle, Robert J; Martin, Gregory R; Raisanen, Jack M; White, Charles L; Foong, Chan; Mickey, Bruce E; Pan, Edward; Hatanpaa, Kimmo J (Journal of neuropathology and experimental neurology, 2018)
Abstract Adult brainstem gliomas are difficult to classify based on radiologic and histologic features. A K27M mutation in histone 3 has been described to identify high-grade midline gliomas associated with a particularly unfavorable prognosis. While initially considered a pediatric entity, it is now known that H3K27M-mutant brainstem gliomas occur in all age groups, but they are less well understood in adults. We studied clinical, radiologic, and pathologic features of 25 brainstem gliomas diagnosed at our institution between 1994 and 2017 in subjects at least 18 years old. Seven tumors (28%) were positive for the H3K27M mutation, and their median overall survival was significantly shorter than in the H3-wildtype group (p = 0.004). Although the mutation was invariably associated with a poor prognosis, our study also illustrates the radiologic and pathologic heterogeneity in this molecular tumor subtype. The results showed that H3K27M-mutant status and clinically aggressive course cannot be ruled out based on low-grade histology on the initial biopsy, exophytic growth, only focal or minimal enhancement or an extrapontine location, such as midbrain or medulla. These results favor an integrated approach employing a combination of clinical, radiologic, histologic features as well as H3K27M immunohistochemistry for the diagnostic subclassification of adult brainstem gliomas.